Self-management in women with stress incontinence: strategies, outcomes and integration into clinical care - Titman, Sarah C (Res Rep Urol, 2019)
The objective of this review is to present and discuss up-to-date conservative treatment strategies for the management of stress urinary incontinence (SUI) in women. This review aims to provide an overview of the importance of initial self-management strategies and conservative management options for women with SUI and how these treatments can be integrated into clinical practice. The various treatment modalities available including pelvic floor physiotherapy, biofeedback, and neuromuscular electrical stimulation devices, in addition to lifestyle changes which can significantly affect symptoms, are discussed. The relevance and importance of individual assessment and training programs is highlighted in addition to additional adjuncts available to facilitate rehabilitation and symptom improvement. Expected outcomes for women with mild to moderate SUI who participate in targeted individualized conservative management programs are generally good, with a high likelihood of substantial improvement in symptoms.